2015
DOI: 10.1186/s40327-014-0015-x
|View full text |Cite
|
Sign up to set email alerts
|

A BIM-based monitoring system for urban deep excavation projects

Abstract: Background Deep excavations in urban areas have the potential to cause unfavorable effects on ground stability and nearby structures. Thus, it is necessary to evaluate and monitor the environmental impact during deep excavation construction processes. Generally, construction project teams will set up monitoring instruments to control and monitor the overall environmental status, especially during the construction of retaining walls, main excavations, and when groundwater is involved. Large volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Related studies are explained next. Wu et al (2015) developed a BIM-based monitoring system to integrate and visualize monitoring data for risk assessment of urban deep foundation pit engineering and verified the effectiveness of the system in the example. Maalek et al (2015) proposed a robust classification and segmentation method based on planar and linear features to improve the accuracy of BIM monitoring system and verified the effectiveness of this method in the laboratory and actual construction site.…”
Section: Introductionmentioning
confidence: 89%
“…Related studies are explained next. Wu et al (2015) developed a BIM-based monitoring system to integrate and visualize monitoring data for risk assessment of urban deep foundation pit engineering and verified the effectiveness of the system in the example. Maalek et al (2015) proposed a robust classification and segmentation method based on planar and linear features to improve the accuracy of BIM monitoring system and verified the effectiveness of this method in the laboratory and actual construction site.…”
Section: Introductionmentioning
confidence: 89%
“…Since the recommendation about the need to integrate risk into nD BIM modelling systems was made by Tah et al (undated), concrete studies on how to systematically simulate risk in an nD modelling environment is lacking. The few studies are Wu et al (2015), Musa et al (2015), Hammad et al (2015), Sun et al (2015), Zou et al (2015), Malvar and Likhitruangsilp (2015). Wu et al (2015) developed a BIM-based risk analytical system for monitoring risk associated with deep excavation projects.…”
Section: Other Related Studiesmentioning
confidence: 99%
“…The few studies are Wu et al (2015), Musa et al (2015), Hammad et al (2015), Sun et al (2015), Zou et al (2015), Malvar and Likhitruangsilp (2015). Wu et al (2015) developed a BIM-based risk analytical system for monitoring risk associated with deep excavation projects. It is important to note that the preceding study did not consider scheduling.…”
Section: Other Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Park et al [23] conducted site safety management in a different way, which demonstrated an automated safety monitoring approach that integrates BLE (Bluetooth Low Energy)-based location tracking, BIM, and cloud-based communication. Wu et al [24] not only concerned about safety management, but also focused on environment protection, which suggest that using various of sensors to monitor the project, then integrate project data, 3D model, stratum data, analysis data and monitoring data into BIM to establish a BIM-based monitoring system for urban deep excavation projects. In site management, sensors can not only conduct process management and safety control, but also helpful for equipment operation.…”
Section: Site Managementmentioning
confidence: 99%